Molecular effects of leptin on peroxisome proliferator activated receptor gamma (PPAR-Î³) mRNA expression in rat's adipose and liver tissue - Abbasi, A.; Moghadam, A. A.; Kahrarian, Z.; Abbsavaran, R.; Yari, K.; Alizadeh, E. (Cellular and Molecular Biology, 2017)
Leptin is a 16-kDa peptide hormone secreted by adipose tissue that participates in the regulation of energy homeostasis. The aim of this study was to determine the effect of leptin injection on mRNA expression of peroxisome proliferator-activated receptor gamma (PPAR-Î³) and comparison of PPAR-Î³ mRNA expression in rat's adipose and liver tissue. Twenty adult male rats were divided into the following groups: Group 1asa control (n=10) that did not receive any treatment. Group 2as a treatment (n=10) that received leptin (30 µg â„ kg BW) intraperitoneally (ip) for two successive days. Blood samples were taken before and one day after second leptin injection for triglyceride (TG), Free Fatty Acid (FFA), HLD-cholesterol, and LDL-cholesterol measurement. Total RNA was extractedfrom the adipose tissue and liver tissues of rats. Adipose and liver tissue cells' cDNA was synthesized to characterize the expression of PPAR-Î³. Gene expression of PPAR-Î³ mRNA was tested by RT- PCR technique. Results show leptin decreases expression of PPAR-Î³ on rat. Low levels of PPAR-Î³ mRNA were detected in adipose and liver tissues of treatment rats in comparison to control group. In treatment group, the level of PPAR-Î³ mRNA in liver tissue was very lower than the adipose tissue. The levels of HDL and FFA in treatment rats were increased whereas serum levels TG, VLDL and LDL were not changed. It is concluded that leptin signal with suppressing of PPAR-Î³ mRNA expression in rat's adipose and liver tissues can result in lipolysis instead of lipogenesis.